INTERNATIONAL TAX HARMONIZATION: A STEP TOWARDS FISCAL JUSTICE - Loso Judijanto; Melyana R Pugu; Mahardika Catur Putriwana Malik; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
International tax harmonization is a global initiative aimed at addressing the challenges and inequities in the current transnational taxation system. With the growth of the global economy and the expansion of multinational corporations, the practice of tax evasion and profit displacement has become a significant problem that reduces national tax revenues and creates inequality among taxpayers. These initiatives include the proposal and implementation of international taxation standards aimed at bridging gaps in domestic and international tax rules used by multinationals to reduce their tax liabilities. Targets for international tax harmonization include the development of common basic rules for the application of corporate profit tax, improved transparency and exchange of information between tax jurisdictions, as well as the introduction of a global minimum corporate tax standard to address the practice of transferring profits to low-tax jurisdiction. While the concept faces challenges such as the need for international consensus and objections from countries that rely on tax revenues as strategic investment incentives, the move is expected to foster a fairer and more efficient tax policy as well as inclusive and sustainable economic growth.